Analysis of spiny lobster fishery sustainability the using ecosystem approach to fisheries management (EAFM) in Pulo Aceh - Ahmad Mukminin; Indra Indra; Muhammad Ali Sarong (Depik, 2022)
The high exploitation rate due to increasing global demand caused spiny lobster vulnerable to overfishing. this study aims to assess the sustainability status of lobster fisheries, through the ecosystem approach to fisheries management (EAFM) and to examine the appropriate strategies to support the sustainability of spiny lobster fisheries in Pulo Aceh Islands, Aceh Besar district, Aceh Province. Indicators or domains used in this study are fish resources, habitats, and ecosystems, fishing techniques, economics, social, and governance, which consist of 27 attributes. Results show that the aggregate value of fish resources domain is 59.22 (moderate), habitat and ecosystem domain is 39.14, (poor), fishing technique domain is 28.62 (poor), the economic domain is 65 (good), social domain is 47.82 (moderate) and the institutional domain is 39.89 (poor). The overall aggregate value for the six domains is 46.61 (moderate), the sustainability status of the spiny lobster fishery in Pulo Aceh is in the moderate category. the fish resource domain and the economic domain are the main domains that provide a positive value for the sustainability of the lobster fishery in Pulo Aceh. However, to improve the status of lobster fisheries management in Pulo Aceh; should focus on domains that have low-value categories, which are; fishing techniques, habitats and ecosystems, and governance domain.Keywords:Spiny LobsterPulo Aceh IslandsSustainabilityManagement Strategy